ETIKA PROFESI GURU PENDIDIKAN LUAR BIASA: TANTANGAN IMPLEMENTASI DAN PENGEMBANGAN PROFESIONALISME DI SEKOLAH LUAR BIASA - Widya Islami Ciptaing Sakti Bakti Sejati, Wangkat; Ruswanto, Alvian; Al Sabrina Ragil, Wassalwa; Tuarlela, Marlina Dorce; Gularso, Dhiniaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Special Education Teachers (SET) face unique complexities in carrying out their professional duties, particularly in implementing professional ethics that align with the needs of students with special needs (SSN) in Special Schools (SLB). Regulations such as Law Number 14 of 2005 concerning Teachers and Lecturers, as well as the Regulation of the Minister of National Education Number 16 of 2007, have not fully addressed the challenges encountered in the field. This study aims to examine the implementation of professional ethics among SET teachers during the learning process, identify the challenges faced in meeting professional ethical standards, and analyze efforts to develop teacher professionalism as a response to these challenges.This study employs a Systematic Literature Review (SLR) of published scientific articles between 2015 and 2026, sourcedaccessed through Google Scholar databases and other credible sources. The findings indicate that although SET teachers possess a deep understanding ofstudents with special needs and professional codes of ethics, their implementation in practice remains suboptimal. The phenomenon of burnout poses a significant threat to the practitioner integrity by teachers in special schools. This study concludes that there is a need for systems that enhance teacher welfare, continuous competency-based inclusive training, and more contextual regulatory updates to ensure that professional ethics among SET teachers can be implemented consistently and with high quality.